Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1179/026708311x13135950699254
|View full text |Cite
|
Sign up to set email alerts
|

White structure flaking (WSF) in wind turbine gearbox bearings: Effects of ‘butterflies’ and white etching cracks (WECs)

Abstract: The actual service life of wind turbine gearboxes is often well below the desired 20 years. One of the prevalent failure modes in gearbox bearing raceways is white structure flaking (WSF) by the formation of butterflies and white etching cracks with associated microstructural change called white etching areas. Despite these failures having been observed for two decades in various industries, the detailed reasons and mechanisms for their formation are not fully understood. In this review, white etching area for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
214
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(224 citation statements)
references
References 129 publications
(598 reference statements)
5
214
0
2
Order By: Relevance
“…This suggests that subsurface fatigue crack growth became sufficiently high enough that the bearing lost its load-bearing capacity. It has been documented that higher than average carbon content in roller bearings, may give rise to WEA, increasing material hardness and providing initiation sites for fatigue cracking [12,46]. This experiment confirmed the significant effect that an overload of 34 kN has on the reduction in life of the selected bearing.…”
Section: Bearing Fatiguesupporting
confidence: 76%
See 1 more Smart Citation
“…This suggests that subsurface fatigue crack growth became sufficiently high enough that the bearing lost its load-bearing capacity. It has been documented that higher than average carbon content in roller bearings, may give rise to WEA, increasing material hardness and providing initiation sites for fatigue cracking [12,46]. This experiment confirmed the significant effect that an overload of 34 kN has on the reduction in life of the selected bearing.…”
Section: Bearing Fatiguesupporting
confidence: 76%
“…It has been observed that subsurface plastic deformation damage in bearings are often associated with butterfly cracking at the white etch area (WEA) [11]. WEA is a region associated with nano-recrystallised carbide-free ferrite [12]. EBSD has been used to measure strain associated with fatigue cracks [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has features of big load capacity, strong radial load carrying ability, small friction between roller and ring race, and can be used for high speed rotation. Because of its special structure, it plays an irreplaceable role in the motor, generator, gas turbine, machine tool spindle and so on [3,4]. With the development of technology and the increasing demand of the main engine performance, the quality of cylindrical roller bearing has been put forward more and more high demand, and its vibration control has become one of the main problems which restrict the quality of this kind of bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows an optical image of a subsurface-initiated WEC in a bearing inner ring, taken during a test in this study. More information about the characteristics of WECs can be found in the literature [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%